Synthesis and Characterization of MnO2 Nanoparticle Composite and Palm Kernel Shell-Based Activated Carbon as Supercapacitor Electrode Candidates - Arif, Ainun Rezkiva; Zakir, Muhammad; Ahmad, Ahyar; Raya, Indah; Taba, Paulina; Rasyid, Herlina (Universitas Gadjah Mada, 2026)
Palm kernel shells (PKS) are a biomass waste rich in carbon and low in ash content, making them suitable for conversion into supercapacitor electrode materials that support the principles of the blue economy and green technology. This study presents a novel synthesis approach for supercapacitor electrode materials by combining activated carbon derived from hydrothermally carbonized PKS biomass waste (AC-PKS) with MnO2 nanoparticles. Carbon activation in this study was carried out using chemical and physical activation approaches to produce a microporous structure with a high surface area. The AC-PKS/MnO2 composite was then synthesized through a redox reaction deposition using KMnO4 to create materials that exhibit potential properties between double-layer capacitance and pseudocapacitive behavior. Electrochemical testing with CV and GCD showed an increase in the specific capacitance of the AC-PKS/MnO2 composite of 67.85 and 46.91 F/g, respectively. These findings indicate the scientific contribution of combining biomass-derived activated carbon with metal oxides as a potential supercapacitor electrode. The implications of these results suggest that AC-PKS/MnO2 not only offers a sustainable material solution but also opens up opportunities for the development of high-capacity supercapacitor electrodes for future energy storage applications, particularly in renewable energy and environmentally friendly technologies.